Comparative evaluation of ultrasonography with magnetic resonance imaging in the diagnosis of shoulder ailments - Krishna Kumar Ningappa Kurnal; Prem Chand Paladugu (Asian Journal of Medical Sciences, 2023)
Background: Shoulder pain encompasses a diverse array of pathologies and can affect as many as one quarter of the population depending on age and risk factors. It may be caused by problems with the neck, glenohumeral joint, acromioclavicular joint, rotator cuff, or other soft tissues around the shoulder. Aims and Objectives: The main aim of the study is to compare the diagnostic accuracy of ultrasound (US) shoulder and magnetic resonance imaging (MRI) of the shoulder in the diagnosis of shoulder ailments. Materials and Methods: This is a comparative study done in Department of Radiology, Aarupadai Veedu Medical College and Hospital, Pondicherry. In total, 54 patients were included for ultrasonography (USG) and MRI examination of shoulder ailments. The statistical analysis was done using Statistical Package for the Social Sciences Version 21.0 statistical analysis software. Results: Subacromial-Subdeltoid Bursitis is the most common finding. US detects partial-thickness tears with a sensitivity of 63.3% and a specificity of 70.8% and full-thickness tears with a sensitivity of 80.0% and a specificity of 91.8%. Trauma was the etiology in only a few patients. MRI is more sensitive than USG in identifying labral and capsular pathologies. MRI is the most sensitive and specific modality for the establishment of shoulder pain. MRI is useful in cases in which the diagnosis is uncertain on USG. Conclusion: MRI is recommended as a secondary method since it provides more information about the extent of tendons and has a lower artifact risk.